Syrians of today, Germans of tomorrow: the effect of initial placement on the political interest of Syrian refugees in Germany - Kassam, Kamal; Becker, Maria (Frontiers in Political Science, 2023)
Syrian nationals are not only the largest refugee group in Germany but also the third largest group of foreigners living in Germany. The naturalization trend among this group has been very pronounced in the last two years and is expected to increase sharply in the coming years. However, little is known about their political interest in German politics.1 Given the importance of “political interest” as an indicator of social integration and future active citizenship, this paper examines the extent to which Syrian refugees are interested in German politics and how local conditions at the time of arrival influence refugees' interest in German politics. We focus on three dimensions of the neighborhood context theory (social networks, economic situation, and political environment) in combination with traditional political participation theory. The empirical strategy relies on the exogenous allocation of refugees across federal states, which can be used to identify the effect of local characteristics on refugees' political interest. We use in our analysis a nationally representative sample in Germany (IAB-BAMF-SOEP-Refugee-Sample). Our findings suggest that ethnic social networks play a significant role in boosting newly arrived refugees' interest in German politics. Moreover, a higher unemployment rate among the foreign population is associated with an increase in political interest among Syrian refugees. We also confirm that a high political interest among the native population in Germany leads to a higher political interest among Syrian refugees. These results show that more attention needs to be paid to the integration of Syrian refugees and underline the need to reassess the efficiency of the distribution policy for Syrian refugees.